Decision Support System for Selection of the Superior Mango Seeds Using Web-based Analytical Hierarchy Process (AHP) Hybrid Simple Additive Weighting (SAW) Method - Noviana; Muslimin B; Suci Ramadhani (Politeknik Pertanian Negeri Samarinda, 2022)
Indonesia is a horticultural country that agricultural production, one of which is mango production. Mango (Mangifera indica L) is one of the leading horticultural commodities in Indonesia. The use of high-quality seeds has made an impact influence on the productivity of farming, to increase the productivity of farming, it is very necessary to provide superior seeds for farmers so that farmers can increase yields and quality of production. With so many manga seeds available, a Decision Support System is needed or often called a Decision Support System (DSS). DSS is a model-based system consisting of procedures in processing and considerations to assist farmers (users) in making decisions on the selection of high-quality manga seeds. In this research, the method used is the Analytical Hierarchy Process (AHP) in searching for the weighting criteria and the Simple Additive Weighting (SAW) method in performing alternative rankings. The results of this study are to make it easier for farmers and the community in choosing superior manga seeds.